Molten salts in nuclear science and technology: a scientometric perspective. (1st January 2014) - Surwase, Ganesh; Mohan, Lalit; Kademani, B.S.; Bhanumurthy, K.
This paper attempts to highlight quantitatively and qualitatively the growth and development of world literature on molten salts in terms of publication output as per INIS database (1972–2011). The objective of the study was to perform a scientometric analysis of all research publications on molten salts in the world. The parameters studied include year-wise growth of publications, country-wise distribution of publications, activity index of top countries, highly productive institutes, language-wise distribution of publications, distribution of publications as per document type, highly preferred journals and identification of highly cited publications on molten salts.